(untitled) (Iter, 2022)
I propose an approach on the ethical and aesthetic cultural treatment given by the ancient Greeks to the ir musical instruments (in this article. the focus of attention is on the aulós and the lyra). Diverse symbolisms (of ethical and aesthetic character) associate with distinct social situations. so that the meaning attributed to the aulós or to the lyra is not ahvay-s the same: one is the meaning attributed to the aulós in the erotic context of the banquet. another one is its meaning in the accompaniment of an athletic or military activity: one is the meaning attributed to the lyra in the educational sphere. another one is its meaning in the funeral imaginary. Amongst the plurality of symbolic contexts. I herein choose to approach one of them: the dichotomy between the lyra and the aulós. in a pedagogical. moral, philosophical and mythological context. which leads us onto a deep symbolic level. which leads us to the opposite pair "culture na ture . This study takes us to a number of possi ble interpretations on identity. memory and ethnicity. Therefore. we shall perceive "beauty" as defining of identity processes. as well as organizer of social memory and ethnic register.